Implementasi Kurikulum Merdeka dalam Pembelajaran di Sekolah: Studi Kasus di SMA Negeri 1 Golewa - Alfares Rae; Rolius Paga Ito; Rosalia Dhiu; Stanislaus Arkineus Kaju; Natalia G. Canera (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the implementation of the Merdeka Curriculum (Kurikulum Merdeka) in the learning process at SMA Negeri 1 Golewa, as well as to identify the supporting factors, obstacles, and strategic solutions in its application. The research employed a qualitative descriptive approach with data collection techniques consisting of observation, in-depth interviews, and documentation. Research subjects were selected through purposive sampling, encompassing the school principal, subject teachers, and students. The findings reveal that the implementation of the Merdeka Curriculum at SMAN 1 Golewa is in a transitional phase, where positive values are beginning to form but have not yet been consistently internalized. The school's strengths lie in its character modality (religiosity, courtesy, and mutual cooperation), while the main challenges center on time and dress code discipline. The active leadership of the school principal proved to be the key factor in encouraging orderliness. This research recommends the development of consistent discipline SOPs, strengthening teacher role models, optimizing learning communities, and synergy with parents of students.